Influence of duration of symptoms over perioperative outcomes during emergency laparoscopic cholecystectomy - Sharma, SK; Thapa, PB; Maharjan, DK; Dhakal, A; Baral, N (Kathmandu University Medical Journal, 2010)
Background: Laparoscopic cholecystectomy is a gold standard treatment for gall stone diseases. Early surgical intervention in acute calculus cholecystitis is feasible and duration of onset of symptoms does not influence the conversion rate. Objective: To compare the safety and feasibility between urgent and delayed laparoscopic cholecystectomy in patients with acute calculus cholecystitis. Materials and methods: This is a comparative study conducted in Department of Surgery, Kathmandu Medical College, during the period of January 2006 to January 2008. Altogether, 436 patients were analysed out of which 55 were selected as urgent laparoscopic cholecystectomy and were included in the study. Among 55 patients presented with acute calculus cholecystitis were divided into two groups. Group 1 underwent laparoscopic cholecystectomy within 72 hours of onset of pain abdomen and Group 2 after 72 hours of onset of pain abdomen. Results: Conversion rate in Group 1 was 19.44% whereas it was 263% in Group 2 (p = .693). There was no statistically significant difference in mean operating time (p = .412), total hospital stay (p = .626), bile duct injury and postoperative complications. Conclusion: Urgent laparoscopic cholecystectomy is safe and duration of onset of pain abdomen does not influence conversion rate. Key words: Urgent laparoscopic cholecystectomy; Conversion rate; acute calculus cholecystitis DOI: 10.3126/kumj.v7i2.2703 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 120-124